Who gets what, a gender analysis of public expenditure in Bangladesh - Evers, Barbara; Siddique, Kaniz (Dhaka : University Press, 2006)
Study based on discussions, various surveys, also workshops; covers the period, 200-2003.
Includes bibliographical references and index.
Keywords: Public expenditures -- Social aspects -- Bangladesh